The Contribution of Art Education to Educational Transitions - Weinlich, Wolfgang (Revija za elementarno izobraževanje, 2018)
The main purpose of this conceptual paper is to place selected areas of art education in parallel with  educational transition. Thus, transition is associated with aesthetic behaviour and aesthet-ic biography, twonotions that may represent two fundamental approaches to art education coined in German / Austrian / Swiss art education theory in recent decades. Both appear to be promising in regard to their potential linkage with transitional education. The study proposes a development in art education that includes and stresses an awareness of transitions; thus, we believe, art education holds great potential to contribute to successful educational transitions throughout early childhood education, kindergarten, school, university and the early phases of professionalization.DOI: 10.18690/rei.11.3.251 -268.2018COBISS-ID:
Keywords: art education; professionalization; transitions